Attribution of profit to permanent establishment in post-BEPS environment - Pessi, Aapo (My University, 2018)
The pro gradu thesis discusses the development of permanent establishment regulation in the field of international taxation, most recently due to the Action 7 of the BEPS project initiated by The Organisation for Economic Co-operation and Development (OECD). BEPS stands for Base Erosion and Profit Shifting, and describes the aim of the project well: to halt international tax avoidance and harmful tax practices. The new regulation and its many channels of implementation will have a material effect on how the multinational corporations shall plan and execute their businesses, resulting in changes in supply chains and operating models. This study aims to detect these changes, and analyze their outcomes regarding existing permanent establishment (PE) structures, and new PE structures created by the changes in regulation. As a separate matter, this study addresses the attribution of profits of the entire business operation between the principal entity and the PE. The research method of this study is the legal dogmatic method. The integral sources of information are the OECD publications regarding the BEPS project, in addition to wide bibliography of Finnish and international tax law literature. Transfer pricing considerations are of essential importance, and therefore, relevant OECD and Finnish administrative guidance is utilized and analyzed. The concluding remarks state that the BEPS project proposes significant changes to the current PE doctrines, but may fall short of its goals of implementation. It is reasonable to assume, however, that the updated PE regulation shall be adopted with time due to OECD’s material influence and EU’s co-operation. In terms of profit attribution the BEPS does not introduce material changes compared to the updated 2017 OECD Transfer Pricing Guidance. Rather, it relies on established principles and methods that were widely used in pre-BEPS structures as well.
Keywords: BEPS, Action 7, OECD, permanent establishment, profit attribution, transfer pricing, tax avoidance, CCCTB, international income taxation